Comparison of pulse pressure and stroke volume variations measured by three monitors in high-risk surgical patients - Cenková, Barbora; Chobola, Miloš; Šrámek, Vladimír; Šitina, Michal; Suk, Pavel (Heliyon, 2024)
INTRODUCTION: Dynamic indices of fluid responsiveness (FR) such as pulse pressure variation (PPV) and stroke volume variation (SVV) differ among hemodynamic monitors, which use proprietary algorithms, and vary even over a short period of time. We aimed to compare the baseline values, fluctuation and predictive value for FR of PPV and SVV measured by three minimally invasive monitors. PATIENTS AND METHODS: Twenty patients undergoing high-risk abdominal surgery were included and 45 fluid challenges were analysed. The patients were simultaneously monitored using Carescape B650, LiDCO Rapid and FloTrac/Vigileo system. Cardiac output (CO), PPV and SVV were recorded before and after the fluid challenge of 500 ml of balanced crystalloid solution. An increase in CO ≥ 15 % defined fluid responders. Concurrently recorded arterial waveform was used for offline calculation of PPV. RESULTS: Mean baseline values of the indices ranged between 8.6 % and 13.4 %. LiDCO showed higher fluctuation of indices compared to the other monitors. Area under the receiver operating characteristic curve (AUROC) ranged from 0.71 to 0.76 with optimal cut-off value between 7.5 % and 13.9 %. AUROC increased for all indices when FR was defined as an increase in stroke volume. Furthermore, a decrease in PPV or SVV after fluid challenge (ΔPPV, ΔSVV) proved a better marker of FR (AUROC 0.82-0.93) than baseline values with a uniform threshold of approximately -3%. CONCLUSIONS: Although a significant range of baselines variations and optimal cut-off values was observed, the predictive value of PPV and SVV from all the monitors was only moderate and comparable. Nevertheless, ΔPPV and ΔSVV appear to be a reliable and device-independent markers of FR.
Keywords: General surgery; Fluid responsiveness; Hemodynamic monitoring; Pulse pressure variation; Stroke volume variation; Pulse wave analysis